Effect of Phytohormone Gibberellic Acid (GA3) on the Germination, Growth and Biomass Production of Persea bombycina - Hazarlka, Swapna Dutra; Sarma, C. M. (Indian Forester, 1999)
The paper presents the results of investigation carried out at the Botany Department, Gauhati University to find the effect of Gibberellic Acid, in yarious strengths, on the germination, growth and biomass of P. bombycina. GA3 at higher concentration enhanced germination rapidly, whereas the biomass yield was higher at lower concentrations.